Future engineers motivating to form basic professional competence - Reznik, Svіtlana; Kuznetsova, Hanna (Institutul Internațional de Management Imi-Nova, 2021)
The current century is characterized by the continuous development of information systems and technologies, that cannot avoid affecting the world economy in general and the economic and production sphere of Ukraine in particular. It is almost impossible to focus only on formally received education under the conditions of the market economy. A high level of professional qualification of a specialist, his fundamental competence in all spheres of life is required. Such a component of the 21st century specialist model as the level of basic knowledge in fundamental disciplines becomes very important. It is the fundamentalization of education that is designed to provide the basic professional competence of a modern specialist, which is becoming increasingly important in the face of growing competition in the labor market and contributes to the economic growth of Ukraine's manufacturing sector. One of the key factors influencing the formation of basic professional competence of future engineers is motivation. The article diagnoses the motivation for the formation of basic professional competence of first-year students of the Faculty of Civil Engineering of the O. M .Beketov National University of Urban Economy in Kharkiv by questionnaire.
Keywords: education; motivation; fundamentalization; professional competence; engineer